The final 19 [videorecording (DVD)] - Breitbach, Timothy; Hefel, Daniel (Buffalo 8, 2023)
This is the horrific and heroic true story of Sgt. Dan Hefel who was of the final 19 POWs to come home from Vietnam. A small town Iowa kid from a large clan of a family, he enlisted following in his nine brother's footsteps. After contracting malaria serving as an infantry grunt he switched to sergeant gunner. What seemed like a prize detail, turned into a nightmare as his helicopter crashed into the mountainside in the dreaded A Shau Valley. Hefel and his crew went from MIA to POWs without the army knowing where they were. Told from both his experience and his family's POV back home, The Final 19 is a rare and deeply intimate personal account of a war that silenced many of its soldiers.